The Ultrasonic Evaluation of Nonfunctioning Thyroid Nodules - Shaub, Michael (1975)
Thyroid echography was carried out on 100 patients with thyroid abnormalities to evaluate the diagnostic accuracy of ultrasound in differentiating simple thyroid cysts from solid thyroid nodules. In all 46 proven cases, the ultrasonic diagnosis of the solid or cystic nature of thyroid nodules was correct. A proposed diagnostic workup of a hypofunctioning (cold) thyroid nodule is suggested with primary needle aspiration and cytologic examination of the cyst fluid being recommended if the nodule is shown to be entirely cystic by ultrasound.